2016
DOI: 10.1097/acm.0000000000001163
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Patients’ Emotions: Teaching Health Care Providers to Interpret Facial Expressions

Abstract: Given the similar baseline performance of faculty and medical students, the ability to interpret facial expressions does not appear to be learned through routine clinical practice, highlighting the need for dedicated facial expression training. The authors were able to demonstrate that physicians and physicians-in-training could effectively learn to recognize emotion by interpreting facial expressions through a short workshop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In another small sample study, Pollux (2016) found large improvements in the ability to recognize subtle facial expressions due to three training sessions with morphed faces showing happy, sad or surprised faces, as well as event-related potential (ERP) modulations in the brain due to training. In a group intervention, Ragsdale et al (2016) presented health care providers with information about facial expression features (i.e., typical muscle contractions) and facilitated three interactive exercises about facial emotional expressions in general and in the medical context. They found a substantial improvement from pre to posttest.…”
Section: Review Of Emotion Recognition Trainings For Healthy Adultsmentioning
confidence: 99%
“…In another small sample study, Pollux (2016) found large improvements in the ability to recognize subtle facial expressions due to three training sessions with morphed faces showing happy, sad or surprised faces, as well as event-related potential (ERP) modulations in the brain due to training. In a group intervention, Ragsdale et al (2016) presented health care providers with information about facial expression features (i.e., typical muscle contractions) and facilitated three interactive exercises about facial emotional expressions in general and in the medical context. They found a substantial improvement from pre to posttest.…”
Section: Review Of Emotion Recognition Trainings For Healthy Adultsmentioning
confidence: 99%
“…According to Darwin and Prodger [4], human facial expressions indicate humans' emotional states and intentions. Recently, automatic emotion detection through computer vision techniques has shown a growth in interest and application across many domains, including hospital patient care [5], neuroscience research [6], smart home technologies [7], and even in cancer treatment [8,9]. This diversity has established emotion recognition as a distinct and growing field in research fields, primarily due to its wide range of applications and intense impact on various phases of human life.…”
Section: Introductionmentioning
confidence: 99%
“…These studies are in favor of the assumption that psychotherapists have greater ERA than other populations. When investigating other mental health professionals (like psychiatrists or nurses), two studies ( Arango de Montis et al, 2014 ; Minardi, 2013 ) found some indication to believe that clinical training or experience leads to increased ERA, whereas another study ( Ragsdale et al, 2016 ) did not find a difference in ERA between medical faculty and medical students. To sum up, the research about psychotherapists’ ERA in comparison to other populations, and about whether ERA improves due to clinical training and experience, is inconclusive and sample sizes are often small.…”
Section: Introductionmentioning
confidence: 99%